PENGEMBANGAN DATA RECORD PASIEN DENGAN METODE JOINT APPLICATION DEVELOPMENT (Studi kasus KLINIK ALFIZA MEDIKA UTAMA) - Muhammad Noval Riswandha; SAIFUL BAHRI (SPIRIT, 2022)
Abstrak: Patient record data or patient data recording is something that exists in every health care facility, which contains records and documents about patient identity, examination, treatment, and actions given to patients which are then stored either in the form of physical documents or computerized, but on Patient data recording often experiences a problem that arises because there is no management of patient data records, causing multiple data records. Multiple data records become a problem point so that it becomes the basis for how to do a solution to multiple patient data records at the Alfiza Medika Utama Clinic. The purpose of the study was to design the development of patient data records using the joint application development method at the Alfiza Medika Utama clinic. This research was conducted using the JAD method because the data collection process involved users, managers and information technology specialists who jointly designed and developed it. The results of which can make it easier for the main Alfiza Medika clinic to record patient data so that there is no more duplicate data and make it easier in terms of services and patients in terms of registration.